Assessing the Influence of Location on the Development of Municipalities - Yusupov, Kasim Nazifovich; Yangirov, Azat Vazirovich; Timiryanova, Venera Maratovna; Toktamysheva, Yuliya Semenovna (Economy of Regions, 2019)
At the present stage, the relevance of the municipalities' interregional cooperation is increasing. This cooperation's development is most needed in the municipalities located on the territories with interregional borders. However, the interregional relations' effective building is hampered by the lack of tools to quantify the effects of the municipalities' location near the interregional border and their dependence on management decisions taken by neighbouring Russian regions. We attempted to quantify how the location and municipality's hierarchical subordination to a particular Russian Federation subject influences its socio-economic status. For analysing group and intergroup relations we applied the tools used in the hierarchical analysis (HLM-Hierarchical linear modelling). We identified the groups of municipalities in accordance with their belonging to Russian subjects and their location (in the subject′s central part or near the interregional border). Further, we analysed 336 municipalities belonging to 7 Russian subjects. 193 of the municipalities are located near interregional borders. The results have proven the tools' applicability in spatial analysis. The calculations have revealed the influence of the municipalities' location on the indicators' achieved values. Additionally, they have allowed us to quantitatively assess the municipalities' significance. Through the data analysis we have determined that some values of the indicators of the location and municipality's hierarchical subordination are influenced more than other ones. The findings can be applied for developing an effective management system for municipalities located near the borders of the Russian subjects.